2017
DOI: 10.1016/j.biopsycho.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The moderating influence of heart rate variability on stressor-elicited change in pupillary and attentional indices of emotional processing: An eye-Tracking study

Abstract: Low resting heart rate variability (HRV) is associated with a broad array of negative psychosocial outcomes. Recent theoretical explications of HRV suggest it is an autonomic marker of emotion regulation capacity, but limited research has examined its relationship with emotional information processing indices. The present study utilized eye-tracking methodology to test HRV’s theorized role as a marker of emotion regulation capacity in a non-clinical sample. Attentional biases towards threatening, dysphoric, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
2
5
0
Order By: Relevance
“…Few studies have explored the direct associations between HRV and the associated pupil response during rest, stress-induced, and meditation phases in clinical samples. Our findings are supported by a recent study by Macatee et al [ 127 ] that examined emotional processing indications of pupillary response and vagally mediated HRV in a nonclinical sample exposed to positive, negative, and neutral stimuli. HRV was unrelated to negative emotional processing and was not significantly associated with the pupillary indices of negative stimuli [ 127 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Few studies have explored the direct associations between HRV and the associated pupil response during rest, stress-induced, and meditation phases in clinical samples. Our findings are supported by a recent study by Macatee et al [ 127 ] that examined emotional processing indications of pupillary response and vagally mediated HRV in a nonclinical sample exposed to positive, negative, and neutral stimuli. HRV was unrelated to negative emotional processing and was not significantly associated with the pupillary indices of negative stimuli [ 127 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are supported by a recent study by Macatee et al [ 127 ] that examined emotional processing indications of pupillary response and vagally mediated HRV in a nonclinical sample exposed to positive, negative, and neutral stimuli. HRV was unrelated to negative emotional processing and was not significantly associated with the pupillary indices of negative stimuli [ 127 ]. In contrast, low HRV predicted decreased pupil dilation to positive stimuli after a stress phase, reflecting altered positive emotional processing following stress induction [ 127 ].…”
Section: Discussionsupporting
confidence: 91%
“…That means, one autonomic process does not necessarily exclude the other, rather both represent different aspects of autonomic activity. In the opposite direction, it has already been shown that CVA can predict decreased pupil size while viewing positive emotional stimuli (Macatee et al, 2017). Therefore, both pupillary responses and CVA seem to present contextdependent adjustments.…”
Section: Discussionmentioning
confidence: 93%
“…As mentioned above, the OFC is an important area responsible for emotional regulation. The lower parasympathetic response predicts poorer mood regulation under an acute stressor ( Macatee et al, 2017 ), so that it may be one of the reasons why the right middle orbitofrontal gyrus in PMS shows a low activation. In addition, previous findings suggest that hormonal fluctuations during the menstrual cycle modulate the brain structure (i.e., OFC), thus influencing negative affect and cognition ( Dubol et al, 2020b ; Dreher et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%